2019
DOI: 10.1038/s41598-018-36887-y
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of volatile and non-volatile pheromone attractants depends upon male social status

Abstract: We investigated the regulation of chemical signals of house mice living in seminatural social conditions. We found that male mice more than doubled the excretion of major urinary proteins (MUPs) after they acquired a territory and become socially dominant. MUPs bind and stabilize the release of volatile pheromone ligands, and some MUPs exhibit pheromonal properties themselves. We conducted olfactory assays and found that female mice were more attracted to the scent of dominant than subordinate males when they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
75
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(85 citation statements)
references
References 98 publications
8
75
1
Order By: Relevance
“…Darcin (MUP20) is a male‐biased protein that is highly expressed in territorial male M. m. domesticus (Roberts et al, ) and M. m. musculus (Thoß et al, ). Our data support these previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Darcin (MUP20) is a male‐biased protein that is highly expressed in territorial male M. m. domesticus (Roberts et al, ) and M. m. musculus (Thoß et al, ). Our data support these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Males are reported to express both genes while females do not (Mudge et al, 2008). Furthermore, higher status males increase expression of Mup20 relative to other MUPs in their urine (Thoß et al, 2019). If semiochemicals are specific to a given species or population, they may also encode information about the species identity or population of origin (Mullen, Mendelson, Schal, & Shaw, 2007).…”
mentioning
confidence: 99%
“…A recent study on wild-derived house mice living in seminatural conditions found that once males acquired a territory and became socially dominant, they increased the production of some (MUP20 and HMH), but not other pheromones (e.g. SBT, DHB, farnesene), whereas males did not reduce pheromone excretion after they became subordinates 24 . Estrous females were more attracted to the urinary scent of dominant, territorial males than subordinates, and variation in protein concentration of male urine had no effect on female preferences when male social status was controlled.…”
Section: Introductionmentioning
confidence: 96%
“…Alternately, status may play a role in the scent, as only dominant wolves have been observed to engage in ground scratching behaviour 51 . In house mice ( Mus musculu s) receptive females showed a preference for the scent from dominant males over the scent of subordinate males 52 .…”
Section: Discussionmentioning
confidence: 99%